When we were bright and beautiful : a novel - Medoff, Jillian (Harper, an imprint of HarperCollinsPublishers, 2022)
"Cassie Quinn may be only twenty-three, but she knows a few things. One: money can't buy happiness, but it certainly doesn't hurt. Two: family comes first. Three: her younger brother, Billy, is not a rapist. When Billy, a junior at Princeton, is arrested for assaulting his on-again, off-again girlfriend, Cassie races home to Manhattan to join forces with her parents and older brother. While certain of his innocence, the Quinns know that Billy fits the all-too-familiar sex-offender profile--white, athletic, and privileged--that makes headlines and sways juries. So as the clock ticks and the law closes in, the family scrambles to hire the best defense money can buy. Meanwhile, Cassie struggles to understand why Billy's ex would go this far, even if the breakup was painful. She knows better than anyone how the end of first love can destroy someone: her own years-long affair with a powerful, charismatic man left her shattered, and she's only recently regained her footing. As reporters converge outside their Upper East Side landmark building, the Quinns gird themselves for a media-saturated trial. Cassie vows she'll do whatever it takes to exonerate her brother. But what if that means exposing her own darkest secrets?"--Dust jacket flap.